Continuous enantiomer‐selective acylation reaction of 1‐phenylethanamine in a magnetic fluidized bed reactor system (MFBRS). Issue 6 (1st April 2019) - Ou, Zhimin; Pan, Jiaying; Tang, Lan; Shi, Hanbing
Abstract: BACKGROUND: Magnetic nanoparticle immobilized enzymes are attractive owing to their potential applications in many biological fields. When an alternating magnetic field is applied, the magnetic moments of the magnetic nanoparticles are apt to align in the direction of the field, and the magnetic nanoparticles experience force in the direction of the field. Thus, the magnetic nanoparticles behave like microscopic stirrers. RESULTS: In this study, (R)‐ N ‐(1‐phenylethyl)acetamide was prepared continuously using immobilized lipase in an alternating magnetic field. The effect of several factors on the acylation reaction were investigated. A kinetic model of the continuous acylation reaction process also was developed. The conversion of 1‐phenylethanamine reached a maximum value of 41.8% with lipase concentration 75 mg mL −1 (dry weight/reaction volume), substrate concentration 500 mmol L −1 and flow rate 25 μL min −1 The enantiomeric excess of (R)‐ N ‐(1‐phenylethyl)acetamide was > 98.4%. The kinetic constants of the continuous reduction were r m = 2.25 × 10 −2 mmol L –1 min −1, k cat = 6 × 10 −4 mmol L –1 min −1, K A = 0.75 mmol L –1 , K B = 4.36 × 10 −3, K QA = 2.43 × 10 −2 and K BQA = 6.2 × 10 −4 mmol L –1 . The kinetic model was in good agreement with the experimental data obtained during continuous acylation reaction. CONCLUSION: The results revealed that the inhibition of the acylation reaction at high substrate concentrations was eliminated during the continuous reaction. Compared with the batch acylation reaction, the continuous acylation reaction showed significantly improved lipase catalyst efficiency. © 2019 Society of Chemical Industry